Contract damages : domestic and international perspectives - Saidov, Djakhongir; Cunnington, Ralph (New Delhi : Mohan Law house, 2008)
This book is a collection of essays examining the remedy of contract damages in the common law and under the international contract law instruments such as the Vienna Convention on Contracts for the International Sales of Goods and the UNIDROIT Principles of International Commercial Contracts. The essays, written by leading experts in the area, raise important and topical issues relating to the law of contract damages from both theoretical and practical perspectives. The book aims to inform readers of current developments, problems, trends and debates surrounding contract damages and reflects
Includes bibliographical references.
eng.
Keywords: Breach of contract; Damages; Export sales contracts